2021
DOI: 10.22201/ia.01851101p.2021.57.01.17
|View full text |Cite
|
Sign up to set email alerts
|

“Head/Tail Plasmon” Produced by a Gaussian Ejection Velocity Pulse

Abstract: We present an analytic model of a collimated ejection with a “single pulse” Gaussian ejection velocity. This flow produces a dense “head” (the leading working surface) joined to the outflow source by a “tail” of lower velocity material. For times greater than the duration of the ejection pulse, this tail develops a linear radial velocity vs. position structure. This “head/tail plasmon” structure is interesting for modelling astrophysical “bullets” joined to their outflow sources by structures with “Hubble law”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Shull & McKee 1979;Dopita & Sutherland 1996;Lehmann et al 2020). Due to collisional ionization of hydrogen, Lyα and Hβ photons are mostly produced in gas at temperatures smaller than T= 10 5 K, with collisional excitation dominating recombination for T> 10 4 K (Raga et al 2015). In the IGM of SQ, it is likely that a wide distribution of shock velocities is present (Guillard et al 2009).…”
Section: Shocks and Turbulent Mixing Layersmentioning
confidence: 99%
“…Shull & McKee 1979;Dopita & Sutherland 1996;Lehmann et al 2020). Due to collisional ionization of hydrogen, Lyα and Hβ photons are mostly produced in gas at temperatures smaller than T= 10 5 K, with collisional excitation dominating recombination for T> 10 4 K (Raga et al 2015). In the IGM of SQ, it is likely that a wide distribution of shock velocities is present (Guillard et al 2009).…”
Section: Shocks and Turbulent Mixing Layersmentioning
confidence: 99%
“…Modelling high speed "bullet" flows in terms of winds, jets and clumps ejected from the central source has been presented by [4,5]. In a recent series of papers [6][7][8], we showed that an ejection pulse with either of the following bulleted points result in the formation of a leading bow shock followed by a tail of material with an approximately linear velocity growth from the source position out to the emitting clump:…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, collisional excitation radiation arises only from neutral gas on the 10 4 K branch. Raga et al (2015) demonstrated that, at 10 5 K, the emission coefficients of Hα and Hβ from collisional excitation are up to five orders of magnitude higher than those due to recombination. This can lead to significant contributions from collisional excitations at these high temperatures even for fairly low Hi fractions.…”
Section: Physical Properties Of the Line-emitting Gasmentioning
confidence: 99%
“…To estimate the extent to which we may be underestimating the photoionised component due to limited resolution, we can estimate the expected Hα luminosity from recombinations of Hii given the incident ionising luminosity of the quasar. For the recombination emission coefficient that we use from Raga et al (2015), together with the rate coefficient for case B recombination used in chimes, we expect that each recombination of Hii will produce 0.27 Hα photons at 10 4 K. If we assume that every incident ionising photon is absorbed and thus leads to one recombination, the resulting Hα luminosity that we would expect given the ionising luminosity is ≈3−4 times higher than that found in the simulations (before radiative transfer effects such as dust attenuation are included). This suggests that we underestimate the photoionised component by a factor ≈3−4.…”
Section: Comparison With Observationsmentioning
confidence: 99%
See 1 more Smart Citation